Analisis Penentuan Komisi Asesor dan Margin Keuntungan Berdasarkan Harga Pokok Penjualan pada PT Adhi Prima Potensia Desember 2024 - Sari Ayu; Asrah Tandirerung Ranteallo (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of assessor commissions and profit margins on the Cost of Goods Sold (COGS) at the consulting service company PT Adhi Prima Potensia during the period of January–December 2024. Consulting firms are unique in that they do not produce physical goods but instead offer expertise-based services, making accurate cost management—particularly in determining COGS—crucial for establishing fair assessor commissions and achieving sustainable profit margins. This research uses a quantitative approach with a descriptive method, collecting data through documentation and interviews regarding the 41 types of consulting services provided by the company. The analysis technique employed is multiple linear regression using SPSS version 25. The results of the study show that both assessor commissions and profit margins significantly impact COGS, both individually (partially) and together (simultaneously). These findings underscore the importance of precise COGS calculations in maintaining cost efficiency, distributing fair compensation, and ensuring the long-term profitability of the company. By highlighting the interconnectedness of commissions, profit margins, and COGS, the study provides valuable insights into how consulting firms can better manage their pricing strategies and cost structures. This research is expected to serve as a useful reference for managerial decision-making, particularly in cost management and strategic pricing, ultimately contributing to the overall growth and sustainability of consulting service firms.